Emha Ainun Nadjib's Qur'an Reception on Maiyah Community - Mukholik, Ayis (Universitas Islam Negeri (UIN) Salatiga, 2022)
This study is aimed to depict Emha Ainun Nadjib's reception of the Qur’an in a religious forum, Maiyah. This research is important to be discussed because Maiyah is an effective forum for transforming religious knowledge, especially the study of the Qur'an to his followers. The researcher uses qualitative research using an anthropological approach. Then, sources of the data were obtained from observations at the Maiyah Islamic forum which was held once a month. The researcher was directly involved in the Maiyah forum to observe Cak Nun and his followers' reception of the Qur'an. Ahmad Rafiq's theory which divides the reception of the Qur'an into three: exegetical reception, aesthetic reception, and functional reception is used to frame the direction of this research. The results of this study are as follows. First, exegetically, Cak Nun and followers of The Maiyah Community perceive the Qur'an as a strategic method of understanding the Qur'an which is comprehended and fit to the general people. Second, aesthetically, the Qur'an in Maiyah is displayed in recitations of the Qur'an and written works of mushaf tadabur which are expressions of Islamic art. Third, functional reception is seen through spiritual and intellectual transformation for followers.